Correspondence,
Letters and postcards from ‘Nora’ c. 1960s; Betsy Thomas; King Harman; ‘Margaret’; ‘Mairead’; Gwendolen Iveagh; Archbishop James Byrne; Msgr. Kissane; Virginia Shaw; Frances Moore; ‘Beth’;Roger Chauviré; ‘Joe’; and M. [Barrau] (in French). Also Christmas card from Leo T. and Georgie McCauley and Archbishop Gerald Thomas Bergan (mentions 1953 visit to Ireland); and compliment cards and notes from Fr. Lennon, Peter Grace and Mons. Domenico Cardini.